ROOST HABITAT SELECTION BY RIO GRANDE TURKEYS IN OREGON - Thomas W. Keegan; John A. Crawford (Wildlife Society Bulletin)
Abstract: We employed a 3‐level hierarchical approach to study roosting habitat of Rio Grande wild turkeys (Meleagris gallopavo intermedia) to increase understanding of habitat needs and provide information for managing forested landscapes in the Pacific Northwest. Roost locations (n = 375) were obtained year‐round (Feb 1989–Jan 1991) from 76 radiomarked females that were part of a recently introduced population (<10 years) in southwestern Oregon. At the largest scale, adult females selected dense, young, mixed‐conifer stands and hardwood‐conifer woodlands (P < 0.05); 58% of roosts occurred in these cover types. Females with broods also selected hardwood‐conifer woodlands (P < 0.05), which accounted for 35% of their roost locations. At the forest stand scale, turkeys typically roosted in trees as large as or larger than others available in the stand. The finest scale was individual roost trees, which averaged 106 years old, 50 cm diameter at breast height (dbh), and 33 m tall. Douglas‐fir (Pseudotsuga menziesii) was the only species used more often than expected for roosting (P < 0.05), comprising 77% of roost trees. To accommodate wild turkey roost habitat needs, timber management plans must include an appropriate juxtaposition and balance of age classes of mixed‐conifer stands over time and in relation to other habitats used by wild turkeys.